Platelet function following trauma - Solomon, Cristina; Traintinger, Stefan; Ziegler, Bernhard; Hanke, Alexander; Rahe-Meyer, Niels; Voelckel, Wolfgang; Schöchl, Herbert (Thrombosis and Haemostasis, 2011)
Platelets play a central role in coagulation. Currently, information on platelet function following trauma is limited. We performed a retrospective analysis of patients admitted to the emergency room (ER) at the AUVA Trauma Centre, Salzburg, after sustaining traumatic injury. Immediately after admission to the ER, blood was drawn for blood cell counts, standard coagulation tests, and platelet function testing. Platelet function was assessed by multiplate electrode aggregometry (MEA) using adenosine diphosphate (ADPtest), collagen (COLtest) and thrombin receptor activating peptide-6 (TRAPtest) as activators. The thromboelastometric platelet component, measuring the contribution of platelets to the elasticity of the whole-blood clot, was assessed using the ROTEM® device. The study included 163 patients, 79.7% were male, and the median age was 43 years. The median injury severity score was 18. Twenty patients (12.3%) died. Median platelet count was significantly lower among non-survivors than survivors (181,000/μl vs. 212,000/μl; p=0.01). Although platelet function defects were relatively minor, significant differences between survivors and non-survivors were observed in the ADPtest (94 vs. 79 U; p=0.0019), TRAPtest (136 vs. 115 U; p<0.0001), and platelet component (134 vs.103 MCEEXTEM – MCEFIBTEM; p=0.0012). Aggregometry values below the normal range for ADPtest and TRAPtest were significantly more frequent in non-survivors than in survivors (p=0.0017 and p=0.0002, respectively). Minor decreases in platelet function upon admission to the ER were a sign of coagulopathy accompanying increased mortality in patients with trauma. Further studies are warranted to confirm these results and investigate the role of platelet function in trauma haemostatic management.Note: This work was carried out at the AUVA Trauma Centre, Salzburg, Austria.
Keywords: Acquired coagulation disorders; haemostasis; platelet pathology / inherited; acquired